(untitled) (Research, Society and Development, 2020)
The following article consisted in the analysis, through bibliographic research, about the duality between civilization and barbarism through the permeation of the criminal state in contemporary times and its relations with the Universal Declaration of Human Rights, using the perspective of the Female Prison System in Brazil. For this analysis were addressed themes related to sexism, racism, capitalism and the restricted action of preeminent human rights in the social and hierarchical status quo which the Penal State maintains. In view of this, the emergence of a punitive culture advocated by political instances reinforces the construction of more “kidnapping institutions” through a manifestation of the State in maintaining hierarchical power in the face of the detainees’ individuality, depriving them of their rights and fixing this subjection to the disciplinary structure in which the lack of basic resources for their physical and psychological health predominates. Thus, the main purpose of the article was to open the discussion about who human rights are concerned about and to question prison institutions through the idea of criminal abolitionism, using studies in Social Psychology and authors such as Michel Foucault, Katie Arguello, Drauzio Varella and Angela Davis.